Regulasi Penegakan Hukum terhadap Pencemaran Air di Sungai Citarum, Jawa Barat - Dhita Amelia (Savana, 2024)
The principle of environmental insight is the principle of capital investment carried out while still paying attention to and prioritizing environmental protection and maintenance. The government in carrying out development must also pay attention to the ecosystem and the surrounding environment. The purpose of this study is to analyze and enforce the law on Citarum River pollution based on the Principle of Environmental Insight, which includes the principles of sustainability, community participation, and environmental responsibility. The method used in this study is normative juridical with qualitative analysis with the data produced in the form of secondary data obtained from previous studies, laws and regulations, and other sources. The results of the study are the Regulation on water pollution in Article 60 of the PPLH Law: "Everyone is prohibited from dumping waste and/or materials into environmental media without permission". Article 104 of the PPLH Law: "Anyone who dumps waste and/or materials into environmental media without permission as referred to in Article 60, shall be punished with imprisonment of a maximum of 3 (three) years and a maximum fine of Rp3,000,000,000.00 (three billion rupiah). Conclusion Law enforcement in environmental issues has been regulated in environmental laws and regulations. Environmental law is a legal rule for every management and protection of the environment. Suggestion The government needs to strengthen regulations related to the disposal of industrial and domestic waste into rivers. Strict and consistent law enforcement must be implemented to ensure that polluters receive appropriate sanctions. Routine inspections and firm action against violators will be important steps